ANTI-FUNGAL ACTIVITY OF KELAKAI LEAF (Stenochlaena palustris (Burm.f) Bedd) - Ratna Widayati; Sarah Novita Rahayu; Helena Jelita (Jurnal Kesehatan Tambusai, 2022)
Candidiasis is a fungal infection caused by Candida albicans. The Kenyah Dayak community in East Kalimantan often use kelakai leaf to treat fungal diseases. The plant contains tannins, flavonoids, steroids that have potential as antifungals. This study aimed to determine the antifungal activity of the ethanolic extract of Kelakai Leaf (Stenochlaena palustris (Burm.f.) Bedd). This research is a laboratory experimental research with post test only control group design. The research subjects used Candida albicans culture, with 7 treatment groups, namely ethanolic extract of kelakai leaf with concentrations of 5%, 15%, 25%, 35% 45%, as well as negative control DMSO and positive control used Fluconazole disc. Antifungal activity was assessed using the Kirby-Bauer disc method, based on the size of the clear zone that occurs. Data analysis using Oneway Anova parametric test. The result of this research is that the ethanolic extract of kelakai leaf can inhibit the growth of Candida albicans with an average inhibition zone of 5% (2.9 mm), 15% (5.4 mm), 25% (7.1 mm), 35% (7.7 mm), 45% (9.3mm). Oneway Anova statistical test results obtained p = 0.000. So it can be concluded that the ethanolic extract of the leaf of Kelakai (Stenochlaena palustris (Burm.f.) Bedd) have an antifungal activity against Candida albicans.